Screening and regulatory mechanisms of biomarkers related to neddylation in laryngeal squamous cell carcinoma - Wang, Xin; Zhang, Haixiang; Wang, Jinping (Frontiers in Molecular Biosciences, 2025)
ObjectiveNeddylation is a crucial posttranscriptional modification involved in tumor progression. This study aimed to explore neddylation-associated biomarkers and the underlying mechanism in laryngeal squamous cell carcinoma (LSCC).MethodsThis study evaluated the expression of neddylation-related genes (NRGs) retrieved from the Reactome and TCGA databases to conduct a series of analyses and constructed an LSCC prognostic risk model followed by functional enrichment and mechanism prediction. Moreover, the key genes involved in this signature were also confirmed in an in vitro cell model.ResultsA total of 79 NRGs were differentially expressed in LSCC (P.adj <0.05). A prognostic gene signature was constructed, and COMMD2, WSB2 and CUL9 were determined to be prognostic genes. The nomogram indicated that this gene signature performed well in forecasting the 1-, 3-, and 5-year overall survival of LSCC patients. The CUL9 and WSB2 genes were enriched in RIBOSOME, and silencing WSB2 significantly inhibited the malignant behaviors of LSCC cells. In this gene signature, patients could be markedly distinguished into high- and low-risk groups characterized by different immune infiltration and drug sensitivity between them. WSB2 and COMMD2 jointly predicted that hsa-miR-185-5p, hsa-miR-4644 and hsa-miR-4306 were the common microRNAs (miRNAs) and regulatory networks.ConclusionThis study successfully established a neddylation-associated prognostic risk model for LSCC and revealed that COMMD2, WSB2, and CUL9 could act as new therapeutic targets, which might provide valuable information for the research and treatment of LSCC.